2009
DOI: 10.1002/cncr.24094
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional recurrence of triple‐negative breast cancer after breast‐conserving surgery and radiation

Abstract: BACKGROUND:The results of radiation on the local control of triple receptor‐negative breast cancer (negative estrogen [ER], progesterone [PR], and HER‐2/neu receptors) was studied.METHODS:Conservative surgery and radiation were used in 753 patients with T1‐T2 breast cancer. Three groups were defined by receptor status: Group 1: ER or PR (+); Group 2: ER and PR (−) but HER‐2 (+); and Group 3: triple‐negative (TN). Factors analyzed were age, menopausal status, race, stage, tumor size, lymph node status, presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
4
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 14 publications
7
85
4
1
Order By: Relevance
“…Nguyen et al (2008) also showed a higher local recurrence rate of 7% in triple negative group when compared with recurrence rates for luminal type A (0.8%) and type B (1.5%) subgroups. Variable results were reported in other studies on TNBC managed with BCT (Nguyen et al, 2008;Freedman et al, 2009;Miller et al, 2009;Voduc et al, 2010). In a recent meta-analysis, Lowery et al (2012) included 12, 592 patients from 15 studies who either received BCT (n=7176) or mastectomy (n=5416).…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al (2008) also showed a higher local recurrence rate of 7% in triple negative group when compared with recurrence rates for luminal type A (0.8%) and type B (1.5%) subgroups. Variable results were reported in other studies on TNBC managed with BCT (Nguyen et al, 2008;Freedman et al, 2009;Miller et al, 2009;Voduc et al, 2010). In a recent meta-analysis, Lowery et al (2012) included 12, 592 patients from 15 studies who either received BCT (n=7176) or mastectomy (n=5416).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported similar results for CSS and a high LRR rate among patients with TNBC. [51][52][53][54][55] Although there are no population-based cancer registries in Mexico, there are some estimates of breast cancer incidence through mortality-specific analyses. On the basis of these findings, the estimated incidence of breast cancer in our country is of 27.2 per 100,000 with a mortality rate of 10.1 per 100,000.…”
Section: -39mentioning
confidence: 99%
“…14 Although loco-regional recurrence, in addition to occurrence of distant metastasis, is known to be more frequent in patients with TNBC, 15,16 the property in application of sentinel lymph node dissection has been discussed insufficiently, 17 and a breast-preserving operation has not been considered as a contraindication for TNBC. 15,18 Tumor recurrence of TNBC has been reported to rapidly increase within 2 years after treatment and to gradually decrease thereafter, and the risk of recurrence and/or death in TNBC is generally low 5 years after initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 Tumor recurrence of TNBC has been reported to rapidly increase within 2 years after treatment and to gradually decrease thereafter, and the risk of recurrence and/or death in TNBC is generally low 5 years after initial diagnosis. Also, in this study the period of tumor recurrence of TNBC after initial treatment was found to be extremely bipolarized.…”
Section: Discussionmentioning
confidence: 99%